Peluang Pengembangan Usaha Sapi Perah di Daerah Dataran Rendah Kabupaten Cirebon - S B Siregar; U Kusnadi (Faculty of Animal Science, Bogor Agricultural University, 2004)
A field study on dairy cattle farms development in low land was conducted in Cirebon district applying a survey method to record all existing dairy cattle farms in the region. Data were collected by interviewing dairy farmers and monitoring the dairy cattle farms. Descriptive approach was applied in data analysis. Constraints would accur, if problems of relatively warm environment in such low land area could not be overcome. Improvements that could be recommended include : an appropriate tropical housing, energy rich feeding and more frequent feeding. Funthermore existing dairy cattle farms in the district should be replaced by dairy types that are resistence to warm environment. Sufficient feed availability and relatively high price of milk should be an optimum condition to enchance dairy cattle development in the said region. In addition, dairy cattle farms is a good opportunity to widely develop and to stimulate by increasing production scale and productivity through improving feeding regimes and adjusting livestock composition to achieve better economic efficiency. Key words: dairy cattle, low land, resources, development